Business Model Canvas: Thelima Printing / Nurul Anis Hafiza Mohamad - Mohamad, Nurul Anis Hafiza (2020)
Thelima Printing is a business that allows people to custom design a shirt (specifically the design on the front or back) any way that they would like. The key partners for Thelima Printing comprise the suppliers, the manufactures, the distributors and the investors. I find the supplier that offer the high quality and the price is affordable. Next, Thelima employees is also important as they are involved in the production of the t-shirt printing whether it is direct or indirect. I rely on them to make sure the products can be produced and promoted well